Island for Sale: Is it Legal? - Priambodo, Bono Budi (UI Scholars Hub, 2018)
For more than ten years already, Indonesian public discourse has been set ablaze by the rumours of Indonesian small islands being sold to foreigners, inviting emotional and, thus, superficial reactions from general public and public authorities alike. This article seeks to offer a conceptual framework to discuss this issue in a more cool-headed manner, thus finding a solution to it. It can be concluded that the problems of small islands are best discussed in the context of coastal areas and small islands (CSI) management, which is the implementation of the Marine Economy policy in order to realize the Archipelagic Outlook. “Island trade,” therefore, is possible under Indonesian law, but more than just transfer of land rights or giving permit to utilize. Instead, it must take into account sustainability, bio-ecoregional as well as participatory considerations.